Análise de aspectos morfológicos e da expressão de timp-1 na cartilagem articular da mandíbula em condição de má oclusão experimental - Mathias, Carolina Brioschi (2018)
Background: The temporomandibular joint (TMJ) can be affected by the same pathological process as the other joints in the human body. Osteoarthritis (OA) is the most common temporomandibular disorder and it is characterized by the degeneration of the cartilage tissue and even the bone below. OA has a complex etiology and disordered occlusion is considered a risk factor because it can create a compression of the cartilage tissue leading to the expression of various cytokines and chemokines, such as the matrix metalloproteinases which activity is regulated by the tissue Inhibitors of the metalloproteinases (TIMP). Among the four existing types of TIMP, TIMP-1 is the most important because it can act as a signaling molecule independent of MMP inhibition thereby influencing important biological processes. Aim: To investigate the responses of mandibular condylar cartilage to experimentally induced disordered occlusion and to evaluate changes in the expression of the TIMP-1 molecule. Methods: Twenty-four female Wistar rats at the age of 8 weeks were enrolled in this study. The animais were randomly divided into experimental and control groups and further divided into four subgroups for two time points (2 and 4 weeks). Experimentally induced sagittal disordered occlusion were created by moving the first molars mesially and distalizing the third molars unilaterally and in opposite sides of the dental arches. At the end of two and four weeks, remodeling of the mandibular condylar cartilage was assessed. Protein expression of TIMP-1 were investigated by means of immunohistochemical staining. The quantitative analysis were made through an image software and statistical analysis by chi-square and Mann-Whitney tests were performed. The statistical significance was defined as P< 0.05. Results: In the 2- and 4-week experimental groups OA-like changes were observed. The most common changes were the increased thickness of the posterior third, disarrangement of the layers disposition, osteoclastic activity and osteophyte formation. Also were found cellular alterations that took form of pyknotic nuclei and condensed cytoplasm chondrocytes and characterize diminution of metabolic activity. The TIMP-1 expression was shown in the mature layers of the control group. However, in the experimental group, immunopositive cells were found in the proliferative and mature layers being that the posterior third of the 2-week experimental group presented a higher levei of TIMP-1-positive cells when compared to the correspondent control (P= 0.0291). Conclusion: The present results indicate that the experimentally created disordered occlusion led to degenerative responses accompanied by changes in the expression of TIMP-1 in mandibular condyle cartilage.